The Bogotá Spirit : South-South Peers and Partners at the Practice-Policy Nexus - Schulz, Nils-Sjard (2012)
On a warm evening in late March of this year, more than 500 enthusiastic delegates from around the world poured out of the Chamber of Commerce building in Bogot, with a shared vision that South-South cooperation would reshape todays development cooperation landscape. Despite the Colombian capitals dizzying altitude of 2,800 meters, their zeal for effective South-South knowledge exchange and mutual learning left the participants of the Bogot High Level Event on South-South cooperation and Capacity Development clear headed and with a long list of ideas, projects and plans, for their countries and regions, and for their multilateral, parliamentary, civil society, and research organizations.